2023
DOI: 10.1007/s11606-022-07995-3
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in Healthcare for Latinx Patients with Limited English Proficiency—a Narrative Review

Abstract: Latinx (includes Hispanics and is the non-gendered term for Latino/Latina which is a person of Latin American origin or descent) constitutes the largest racial and ethnic minority group in the United States (US). Many members of this group report limited English proficiency, experience discrimination, feel distrust in the healthcare setting, and face poorer health outcomes than non-Latinx Whites. As healthcare systems assess internal structures of care, understanding the experiences of Latinx patients may info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…Our findings are consistent with multiple studies demonstrating access barriers faced by patients with LEP that may contribute to underutilization of care and negative health outcomes. 4 , 6 , 38 Further, our finding that 38% of clinics listed in online provider directories could not be reached by any of our callers or were not taking new patients provides further evidence of the existence of “ghost networks” (ie, providers who are listed by payers as in-network options but are nonexistent or unavailable) in behavioral health. 39…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Our findings are consistent with multiple studies demonstrating access barriers faced by patients with LEP that may contribute to underutilization of care and negative health outcomes. 4 , 6 , 38 Further, our finding that 38% of clinics listed in online provider directories could not be reached by any of our callers or were not taking new patients provides further evidence of the existence of “ghost networks” (ie, providers who are listed by payers as in-network options but are nonexistent or unavailable) in behavioral health. 39…”
Section: Discussionmentioning
confidence: 67%
“… 3–5 Compared with English-proficient patients, patients with LEP receive fewer health care services, have greater unmet mental health needs, and receive poorer quality care. 6 , 7 The challenges start well before patients with LEP interact with the health care system: patients with LEP with a mental health condition are less likely to perceive a need for treatment or seek specialty behavioral health treatment. 8 Recent studies have identified factors contributing to inequities in access and outcomes for Spanish-speaking patients, including lack of language services, perceived discrimination, and mistrust and privacy concerns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…124 Studies have also revealed that minority groups, such as African Americans, Asian Americans, and Hispanics/Latinos seek hospice care less frequently. 125 Cultural variations in the impact of the disease or its mitigation and palliative care among different sections of patients and their families are also often variable in the western world as compared to close-knit societal frameworks as seen in South Asia, Southeast Asia, and the far East. Buddhism's predominant faith in "natural fate" urges sufferers to face pain as they await death.…”
Section: Disparities In Palliative Carementioning
confidence: 99%
“…The population demographics continue to evolve, and many ethnic groups are growing rapidly. Presently, the Latinx population constitutes the largest racial and ethnic minority group in the United States (3), comprising approximately 18.9% in 2020 and is projected to constitute 28% of the country by 2060 (4). Importantly, as much as 70% of this population speaks a language other than 1 Division of Internal Medicine, University of Toronto, Toronto, Ontario, Canada; 2 Office of Clinical Research, Baptist Health South Florida, Miami, Florida, USA; 3 English at home, and 28.4% are not fluent in English (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%